Sexually-transmitted infections: What´s new about the control of chlamydia trachomatis - Damiani, Maria Elena (2019)
Chlamydia trachomatis (Ctr) is the most common bacterial cause of sexually transmitted infections (STIs). The World Health Organization (WHO) estimates that 131 million are infected each year, mainly young people of reproductive age. In women, Ctr causes cervicitis, endometritis, salpingitis, which frequently persist along time leading to serious complications such as pelvic inflammatory disease, spontaneous abortions and tubal infertility. Newborns, when infected in the birth canal, can develop conjunctivitis and pneumonia; whereas men can suffer urethritis, prostatitis, and epididymitis. Ctr is the main cause of preventable blindness or trachoma worldwide. There was an epidemiological alert in Argentina in August 2018 for the appearance of venereal lymphogranuloma. The asymptomatic nature of most of the infections makes diagnosis and treatment difficult. Besides, the lack of a preventive vaccine and the antibiotic resistance increase reveal the need for new tools for the prevention and control of chlamydial infections. Ctr invades cervical epithelial cells through numerous receptors, many of them glycosylated, and survives and multiplies intracellularly in a vesicle called inclusion. We have shown the release of a glycan-binding protein, galectin 1 (Gal1), in cervical tissues under inflammation. This lectin engages glycosylated bacterial proteins, like MOMP (Major Outer Membrane Protein) and OmcB, to glycosylated cervical epithelial cell receptors such as PDGFR and various integrins. Acting as a bridge between bacterial and eukaryotic glycans, Gal1 promotes invasion, increasing not only the number of infected cells but also the number of inclusions per cell and the number of bacteria per inclusion. Lactose, glycanases or neutralizing antibodies against glycosylated receptors decrease the magnitude of chlamydial infections. In agreement, mice KO for complex N-glycan-forming enzymes and Gal1 are less susceptible to infection. These findings suggest that hijacking bacterial glycan-Gal1-glycosylated receptors bridge could be a new tool to prevent cell invasion and overall Ctr infection. Once inside the cell, Ctr avoids its degradation in the phagocytic pathway by hijacking Rab proteins, the main controllers of intracellular transport. By bacterial-driven mechanisms, certain Rabs are recruited to the chlamydial inclusion while others are excluded. We have described that Ctr intercepts Rab14-mediated transport not only to evade fusion with lysosomes but also to acquire sphingolipids synthesized at the Golgi apparatus. Molecular mechanisms underlying how these bacteria manipulate intracellular transport are a matter of intense study. We demonstrate that Ctr provokes Akt phosphorylation along its entire developmental life cycle and recruits phosphorylated Akt (pAkt) to the inclusion membrane. As a consequence, Akt Substrate of 160 kDa (AS160), also known as TBC1D4, a GTPase Activating Protein (GAP) for Rab14, is phosphorylated and therefore inactivated. Phosphorylated AS160 (pAS160) loses its ability to promote GTP hydrolysis, favoring Rab14 binding to GTP. Akt inhibition by an allosteric isoform-specific Akt inhibitor (iAkt) prevents AS160 phosphorylation and reduces Rab14 recruitment to chlamydial inclusions. iAkt further impairs sphingolipids acquisition by Ctr-inclusion and provokes lipid retention at the Golgi apparatus. Consequently, treatment with iAkt decreases chlamydial inclusion size, bacterial multiplication, and infectivity in a dose-dependent manner. Similar results were found in AS160-depleted cells. By electron microscopy, we observed that iAkt generates abnormal bacterial forms as those reported after sphingolipids deprivation or Rab14 silencing. Taken together, our findings indicate that targeting the Akt/AS160/Rab14 axis could constitute a novel strategy to limit chlamydial infections, mainly for those caused by antibiotic-resistant bacteria.